The twilight of the British Empire British intelligence and counter-subversion in the Middle East, 1948-63 - Chikara, Hashimoto (Intelligence, surveillance and secret warfare, 2019)
This book reveals, for the first time, a hitherto unexplored dimension of Britain's engagement with the post-war Middle East: the counter-subversive policies and measures conducted by the British Intelligence and Security Services and he Information Research Department (IRD) of the Foreign Office, Britain's secret propaganda apparatus